IMPLEMENTASI KEBIJAKAN PEMERATAAN MUTU PENDIDIKAN DI KECAMATAN PAMONA BARAT KABUPATEN POSO - MBAE, AGHNES TRESYA; OGOTAN, MARTHA; PALAR, NOVIE ANDERS (Sam Ratulangi University, 2018)
Based on Law No. 20 of 2003 concerning the National Education System, article 5 paragraph (1) statesthat